1985
DOI: 10.1111/j.2042-7158.1985.tb03070.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the bioavailability of five different phenytoin preparations

Abstract: The concentration of phenytoin in saliva has been measured in 8 healthy volunteers at intervals after an intravenous dose and after single oral doses of five formulations commercially available in the United Kingdom. The six doses (all 300 mg) were given in random order and at least one week apart. There were no significant differences in the mean values of the peak saliva concentration, the time-to-peak and the area under the saliva concentration-time curve between the five oral formulations. The absolute bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 10 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…31 More recent studies on bioequivalence have reported differences in pharmacokinetic parameters between generic phenytoin and the innovator brand, 30,66,67 though some of these differences were small and considered unlikely to have clinical consequences. 29,68 Differences in the content of phenytoin between capsules of generic and branded preparations, rather than differences in the pharmacokinetics per se, have also been reported. 31 Differences in pharmacokinetic parameters between branded and generic formulations have been reported in Chinese subjects 69 and when taken with food, 16 which could have clinical implications.…”
Section: Experience With Generic Substitution Of Phenytoinmentioning
confidence: 99%
See 1 more Smart Citation
“…31 More recent studies on bioequivalence have reported differences in pharmacokinetic parameters between generic phenytoin and the innovator brand, 30,66,67 though some of these differences were small and considered unlikely to have clinical consequences. 29,68 Differences in the content of phenytoin between capsules of generic and branded preparations, rather than differences in the pharmacokinetics per se, have also been reported. 31 Differences in pharmacokinetic parameters between branded and generic formulations have been reported in Chinese subjects 69 and when taken with food, 16 which could have clinical implications.…”
Section: Experience With Generic Substitution Of Phenytoinmentioning
confidence: 99%
“…P. Crawford et al This potential for differences in therapeutic response to AEDs, even though products are defined as bioequivalent, is a recurring theme in the literature, 1,2,5,6,19,23,24,[26][27][28][29][30][31] with a number of issues highlighted.…”
mentioning
confidence: 99%